2005
DOI: 10.1111/j.1467-9310.2005.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate technology portfolios and R&D performance measures: a study of technology intensive firms

Abstract: This paper examines the relations between technology portfolio strategies and five commonly used research and development (R&D) performance measures. Patent and financial data of 78 US‐based technology companies from 1976 to 1995 were gathered and analysed to investigate how a well‐managed technology portfolio can create synergy and affect R&D performance. A technology portfolio can be characterized by its composition and technology concentration. A valuable technology portfolio that consists of patents with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 28 publications
3
84
0
Order By: Relevance
“…According to Dicle and Kose [19], deliberate and continuous learning adds flexibility to an organisation's effort to generate and commercialise new products. The learning orientation is an organisational process of creating customer-and competitor-related knowledge, and determining the method of collecting, sharing and interpreting the obtained knowledge [20,21]. A welldesigned organisational learning orientation -supported by learning objectives, a continuous commitment of resources, and a culture of information-sharing -serves its purpose well.…”
Section: Organisational Learning Orientation and Product Innovation Pmentioning
confidence: 99%
“…According to Dicle and Kose [19], deliberate and continuous learning adds flexibility to an organisation's effort to generate and commercialise new products. The learning orientation is an organisational process of creating customer-and competitor-related knowledge, and determining the method of collecting, sharing and interpreting the obtained knowledge [20,21]. A welldesigned organisational learning orientation -supported by learning objectives, a continuous commitment of resources, and a culture of information-sharing -serves its purpose well.…”
Section: Organisational Learning Orientation and Product Innovation Pmentioning
confidence: 99%
“…On the other hand, researchers acknowledge that the relationship between technological diversification and performance is not linear as the technological diversification increases, but rather, curvilinear of inverted-U, because of the correlation between the synergy among resources and the management cost [16,[34][35][36]. It is also found that a firm has the features of conditional opposition by the moderators such as the firm's absorptive capacity, technological relatedness, technological capabilities, and firm's size [5,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…We also deal with how to modify strategies dynamically. such as the firm's absorptive capacity, technological relatedness, technological capabilities, and firm's size [5,[37][38][39]. One of the possible explanations for why there is no clear consensus on this topic is that insufficient consideration has been given to two important factors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although it is widely agreed that technological innovation is the most powerful source of competitive advantage, the value created by skyrocketing R&D expenditures is sometimes seriously challenged (Mank and Nystrom, 2001). Technology-based firms often struggle for the effectiveness and efficiency of their R&D functions (Lin & Chen, 2005).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%